Dinamika Stres dan Konflik di Perpustakaan: Pendekatan Negosiasi untuk Meningkatkan Kualitas Layanan - Santi, Triana (IQRA`: Jurnal Perpustakaan dan Informasi, 2025)
This research aimed to explore the dynamics of stress and conflict within the library environment of Medan City and to analyze the role of negotiation approaches as a strategy to mitigate their negative impacts on service quality. Employing a sequential exploratory mixed- methods design (qualitative-quantitative), the research involved librarians and service users from various types of libraries in Medan City. The qualitative phase identified excessive workload, user demands, and resource limitations as primary sources of stress and conflict, alongside dominant informal negotiation practices. The quantitative phase confirmed that levels of stress and conflict frequency significantly correlated negatively with user perceptions of service quality. However, regression analysis and t-tests revealed that the use of integrative negotiation strategies by librarians significantly predicted lower stress levels, better conflict management, and higher perceived service quality. These findings are supported by the Transactional Theory of Stress, Realistic Conflict Theory, Integrative and Distributive Negotiation Theory, and the SERVQUAL Model. The study concludes that developing integrative negotiation skills represents an effective strategic intervention for enhancing librarian well-being and library service quality in Medan City.